2010
DOI: 10.1051/0004-6361/200913882
|View full text |Cite
|
Sign up to set email alerts
|

Absolute proper motion of the Galactic open cluster M 67

Abstract: We derived the absolute proper motion (PM) of the old, solar-metallicity Galactic open cluster M 67 using observations collected with CFHT (1997) and with LBT (2007). About 50 galaxies with relatively sharp nuclei allow us to determine the absolute PM of the cluster. We find (μ α cos δ, μ δ ) J2000.0 = (−9.6 ± 1.1, −3.7 ± 0.8) mas yr −1 . By adopting a line-of-sight velocity of 33.78 ± 0.18 km s −1 , and assuming a distance of 815 ± 50 pc, we explore the influence of the Galactic potential, with and without th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 30 publications
(44 reference statements)
5
57
1
1
Order By: Relevance
“…Our best estimate of the age of M67-1194 (4.2 ± 1.6 Gyr) agrees very well with determinations based on alternative methods. Most fits of isochrones to the M67 color-magnitude diagram, whether using Garching (see Magic et al 2010), Montreal (Michaud et al 2004), Padova (Yadav et al 2008), Teramo (Bellini et al 2010), Victoria (VandenBerg et al 2007), or YaleYonsei (Yadav et al) isochrones, favour an age of 4.0 ± 0.3 Gyr. Moreover, Bellini et al have recently found that the age obtained from the cluster white dwarfs is fully consistent with the aforementioned turnoff age.…”
Section: The Age Of M67mentioning
confidence: 99%
“…Our best estimate of the age of M67-1194 (4.2 ± 1.6 Gyr) agrees very well with determinations based on alternative methods. Most fits of isochrones to the M67 color-magnitude diagram, whether using Garching (see Magic et al 2010), Montreal (Michaud et al 2004), Padova (Yadav et al 2008), Teramo (Bellini et al 2010), Victoria (VandenBerg et al 2007), or YaleYonsei (Yadav et al) isochrones, favour an age of 4.0 ± 0.3 Gyr. Moreover, Bellini et al have recently found that the age obtained from the cluster white dwarfs is fully consistent with the aforementioned turnoff age.…”
Section: The Age Of M67mentioning
confidence: 99%
“…Examples are in Carraro & Chiosi (1994), while open cluster orbits have been calculated several times in the past (see e.g. Bellini et al 2010;or Carraro et al 2006, for recent examples). However, in all past cases, no effect of the bar could be seen because of the mean large distance of the clusters from the GC and the relatively small sphere of influence of the bar.…”
Section: The Orbits Of the Inner Ocsmentioning
confidence: 99%
“…Accordingly, significant efforts have recently been invested in successfully modeling the observed properties of several white dwarf populations with a high degree of realism. These include the Galactic disk and halo -see the very recent works of Cojocaru et al (2014Cojocaru et al ( , 2015 and references therein -and the system of Galactic open Article published by EDP Sciences A35, page 1 of 8 Bellini et al 2010;Bedin et al 2010) and globular clusters (Hansen et al 2002;García-Berro et al 2014;Torres et al 2015).…”
Section: Introductionmentioning
confidence: 99%